Der demografische Wandel und die Nachfrage nach Flugurlaubsreisen. Unterschiedliche Perspektiven für die einzelnen Regionen Deutschlands. - Pak, Henry (Deutscher Verkehrs-Verl., 2007)
Urlaubsreisen der Deutschen zu Zielen ins europäische und außereuropäische Ausland bilden seit langem das größte Segment der Luftverkehrsnachfrage in Deutschland. Laut Fluggastbefragungen machten sie im Jahr 2003 mit einem Volumen von 23,9 Mio. Reisen nahezu die Hälfte der Luftverkehrsnachfrage aus. Wird das so bleiben? difu

The consequences resulting from Germany's demographic changes - coupled with their impact on transport generally - increasingly provide a basis for analyses and discussions. The air transport market is going to be affected by these changes since about three quarters of the demand (transit traffic excluded) is generated in Germany. Holiday travel by air currently forms by far the largest market segment whose future development will be influenced not only by changes in population but also by people's attitude towards holidays. This report deals with the impact of regional changes in population on airports and airlines. difu
Keywords: Verkehr; Verkehrsverhalten; Befragung; Luftverkehr; Urlaubsverkehr; Verkehrsnachfrage; Verkehrsprognose; Verkehrsplanung; Regionale Disparität; Verkehrsforschung; Flugtourismus